Gambir (Uncaria gambir Roxb) as Natural Cosmeceutical Agent - Setyowati, Hanny (PT. Kalbe Farma Tbk., 2017)
Uncaria gambir contains varying amounts of polyphenols, mainly catechins. Catechin has a photo-protection activity which can be applied as sunscreen. The future goal of this cosmeceutical product is to prevent skin photo-damaging by UV-radiation.Uncaria gambir mengandung banyak komponen polifenol, terutama catechin. Catechin, sebagai senyawa utama tanaman gambir, memiliki aktivitas perlindungan terhadap cahaya matahari sehingga dapat diaplikasikan dalam sediaan tabir surya.Â